Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles